2012
DOI: 10.1007/s12325-012-0028-6
|View full text |Cite
|
Sign up to set email alerts
|

Are Dosing Adjustments Required for Colchicine in the Elderly Compared with Younger Patients?

Abstract: Introduction:The objective of this study was to

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 11 publications
0
6
0
Order By: Relevance
“…16 It should be noted, however, that the results of a recently published trial showed that dosing adjustments are not required in healthy elderly patients 60 years of age or older with mild renal impairment receiving colchicine 0.6 mg for acute gout flares. 17 In this study, following the singledose administration of colchicine 0.6 mg, there were no clinically meaningful differences in CL/F total body clearance parameters in patients (i.e., maximum plasma concentration [C max ], area under the drug concentrationtime curve [AUC], half-life, and CL/F, including those with mild renal impairment. Colchicine 0.6 mg was also equally well tolerated in both patient groups.…”
Section: Overview Of Gout Management and The Role Of Colchicinementioning
confidence: 68%
“…16 It should be noted, however, that the results of a recently published trial showed that dosing adjustments are not required in healthy elderly patients 60 years of age or older with mild renal impairment receiving colchicine 0.6 mg for acute gout flares. 17 In this study, following the singledose administration of colchicine 0.6 mg, there were no clinically meaningful differences in CL/F total body clearance parameters in patients (i.e., maximum plasma concentration [C max ], area under the drug concentrationtime curve [AUC], half-life, and CL/F, including those with mild renal impairment. Colchicine 0.6 mg was also equally well tolerated in both patient groups.…”
Section: Overview Of Gout Management and The Role Of Colchicinementioning
confidence: 68%
“…It is interesting that several studies have reported different elimination half‐life of colchicine including the mean T 1/2 ‐9 h, 16 h and recently 25 h . On the other hand, although there is no clear‐cut serum colchicine level showing toxicity or therapeutic range, below 2.5 ng/mL was reported as a non‐toxic level .…”
Section: Discussionmentioning
confidence: 99%
“…Almost 10–20% of colchicine remains unchanged and is excreted in the urine . This drug has a narrow therapeutic index having no certain non‐toxic, toxic, or lethal dose; however, routine dose reduction has been recommended in renal failure patients, the elderly, and patients with chronic liver disease to avoid toxicity . Moreover, there are several drugs that can cause inhibition of CYP3A4 and P‐glycoprotein, such as cyclosporin, tacrolimus, diltiazem, macrolides, fluconazole, lovastatin, donepezil, and dapsone .…”
mentioning
confidence: 99%
“…At doses of 0.5 mg/d, colchicine may induce GI intolerance in up to 10% of the people during the first month of treatment; however at this dose, long-term therapy is known to be otherwise safe and well tolerated in children, 81 the elderly individuals, 82 and during pregnancy. 83 At doses of up to 2 mg/d, there have been rare case reports of reversible peripheral neuritis and myopathy, 84 alopecia, 85 inhibition of spermatogenesis but not fertility, 86 B12 deficiency, 87 and bone marrow suppression.…”
Section: Preventing Cholesterol Crystal-induced Inflammationmentioning
confidence: 99%